Obowiązek rejestracji prasy a postęp technologiczny - Goździaszek, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of the article is to show the evolution of the requirements related to publishing the press and to define the directions of new legal changes. The current regulations are inadequate to the contemporary realities of the media market and communication possibilities. The obligation to register the press can be seen as a relaxed follow-up to the authoritarian or totalitarian regimes’ requirement to obtain a license to publish a journal or a periodical. Press registration would be a democratic alternative to obtaining a press license only if certain values supported it, including the interests of other persons and entities. Currently, such interests are secured by other regulations. The considerations of the courts and legal science focus on the possible contradiction of the current regulation on the registration of newspapers and magazines with the constitutional ban on licensing the press. However, it should be taken into account to a greater extent that the dissemination of the internet and computer hardware has made it more complicated to register a periodical than to start a simple press activity. Therefore, the obligation to register the press in its present form is unreasonable.
Keywords: prasa; media; rejestracja; internet; prawo